Christian reflection in Africa : review and engagement - Bowers, Paul. (Carlisle : Langham Global Library, 2018)
This reference collection presents academic reviews of more than twelve-hundred contemporary Africa-related publications relevant for informed Christian reflection in and about Africa. The collection is based on the review journal BookNotes for Africa, a specialist resource dedicated to bringing to notice such publications, and furnishing them with a one-paragraph description and evaluation. Now assembled here for the first time is the entire collection of reviews through the first thirty issues of the journal's history. The core intention, both of the journal and of this compilation, is to encourage and to facilitate informed Christian reflection and engagement in Africa, through a thoughtful encounter with the published intellectual life of the continent. Reviews have been provided by a team of more than one hundred contributors drawn from throughout Africa and overseas. The books and other media selected for review represent a broad cross-section of interests and issues, of personalities and interpretations, including the secular as well as the religious. The collection will be of special interest to academic scholars, theological educators, libraries, ministry leaders, and specialist researchers in Africa and throughout the world, but will also engage any reader looking for a convenient resource relating to modern Africa and Christian presence there.
Includes bibliographical references and index.
Keywords: Theology, Doctrinal -- Africa; Africa -- Church history